Development and validation of a simple and rapid UPLC method for the in-vitro estimation of (-)-epigallocatechin-3-gallate in lipid-based formulations - El-Kayal, Maha Osama; Sayed, Maha Nasr; Mortada, Nahed Dawood; Elkheshen, Seham (European Journal of Chemistry, 2018)
(-)-Epigallocatechin gallate (EGCG) is a catechin found in green tea that has potential health benefits, such as anti-oxidant, anti-carcinogenic and anti-inflammatory effects. A rapid and sensitive Ultra-Performance Liquid Chromatographic (UPLC) method was developed and validated for the estimation of (-)-epigallocatechin-3-gallate in lipid-based formulation. The UPLC method was conducted on C18 analytical column (50 mm × 2.1 mm, 1.8 μm particle size). The mobile phase consisted of a mixture of acetic acid (1%, v:v; pH = 3), acetonitrile and water at volume ratio of 13:15:72 delivered at a flow rate of 0.5 mL/min. The diode array detector (DAD) acquisition wavelength was set at wavelengths 210 and 280 nm. Caffeine was used as internal standard. The tested validation parameters, i.e., selectivity, linearity, accuracy, precision, and sensitivity (Limit of detection and limit of quantification) were determined at both wavelengths. Results revealed that caffeine and EGCG peaks were eluted at retention times of 0.55 and 0.85 minutes, respectively. The calibration curve was linear over the concentration range of 10-60 μg/mL, with coefficients of determination (r2) of 0.9993 and 0.9998 nm at 210 and 280 nm, respectively. All the validation parameters were found within the acceptable range. The proposed method was successfully applied for the quantitation of EGCG in lipid-based formulation and statistical analysis with a reported method showed no significant difference at p < 0.05. Therefore, the proposed analytical method for EGCG can be considered as a rapid, selective and accurate analytical method that can be used for the quantitative analysis of EGCG.